Technology readiness, customer perceived value, customer information satisfaction and behavioral intention on tablet-based menu ordering experience / Muhammad Izzat Zulkifly - Izzat Zulkifly, Muhammad (2017)
It is a common practice among restaurateurs to provide menu cards as a medium of communication to speak about their menu items. Many limitations have been identified from the use of this method of menu ordering such as customer indecision and other forms of service failures. Tablet-based menu ordering system which is 'selfservice' in nature is gaining popularity among restaurants due to its capacity to handle descriptive menu, other information and illustration as well as other interactive options and many other benefits. The success of this system depends on how restaurants balance the use of technology and human touch. Too much dependency on technology would take away the human-touch value which is important in a foodservice operation. Not much is known about Malaysian customers' technology readiness and how they perceived the value offered by this system, thus it is difficult to figure out the effectiveness of the system based on their information satisfaction on the menu ordering experiences which will then influence customers' behavioural intention. This study empirically investigates the causal relationship between technology readiness, customer perceived value, customer information satisfaction and behavioural intention towards the tablet-based menu ordering system. A quantitative investigation through survey questionnaire among customers who already had the experience was conducted. Data from a total of 421 respondents were analyzed through the process of multivariate analysis using Structural Equation Modelling (SEM) via Analysis of Moment Structures (AMOS). The exploratory factor analysis (EFA) and later the confirmatory factor analysis (CFA) validated the scales used in the study. The results suggest that all constructs; technology readiness, customer perceived value, customer information satisfaction and behavioural intention were significantly related. The strength between technology readiness and customer information satisfaction would change with the presence of customer perceived value. Similarly, the relationship strength between customer perceived value and behavioural intention was altered when customer information satisfaction was included. These concluded that customer perceived value mediate the first relationship while customer information satisfaction mediates the latter. Malaysian customer can accept this kind of ordering experience and other restaurants should see this as an opportunity to invest on the system. Finally, the implications of the findings are discussed, and future research directions are recommended.